Effect of water and nitrogen application under mulched drip irrigation on growth, yield and quality of spring soybean - WANG Yue; HE Xianggui; XIE Haixia; ZHOU Jianpin; WANG Shuyu (Guan'gai paishui xuebao)
【Background and Objective】In 2023, Xinjiang initiated a project to cultivate 66 700 hectares of spring soybeans. Due to its arid and semi-arid climate, soybean production in Xinjiang depends heavily on irrigation and fertilization. Understanding the combined effects of water and nitrogen under mulched subsurface drip irrigation is critical for optimizing the use efficiency of these inputs and providing technical guidance for soybean production.【Method】A field experiment was conducted using the soybean variety Yongnong 3 in a split-plot design. The experiment included three irrigation amounts: 3 600 m3/hm2 (W1), 4 500 m3/hm2 (W2), and 5 400 m3/hm2 (W3). Each irrigation treatment was paired with four nitrogen applications: no nitrogen (N0), 138 kg/hm2 (N1), 207 kg/hm2 (N2), and 276 kg/hm2 (N3). During the experiment, we measured and analyzed crop growth, yield and grain quality.【Result】① Increasing irrigation amount significantly promoted crop growth. Dry matter accumulation over time followed a logistic growth curve, with rapid accumulation observed between the pod-setting and grain-filling stages. ② Irrigation and nitrogen application had significant effects on crop growth and yield components. Dry matter accumulation, yield, and yield components increased with irrigation amount. Among all nitrogen treatments, 138 kg/hm2 (N1) resulted in the highest dry matter accumulation and yield. ③ The highest dry matter accumulation (11 233.53 kg/hm2) and grain yield (5 685 kg/hm2) were achieved with 5 400 m3/hm2 of irrigation (W3) and 138 kg/hm2 of nitrogen application (N1). Compared to W1N0, this combination increased grain yield by 132.04%, pods per plant by 164.57%, grains per plant by 134.13%, grain weight per plant by 227.22%, main stem node count by 25.06%, and 100-grain weight by 24.31%. ④ While increasing irrigation did not significantly affect protein and fat content, nitrogen application increased protein content but reduced fat accumulation.【Conclusion】In the arid and semi-arid regions of Xinjiang, effective irrigation and nitrogen management are crucial for optimizing soybean growth and yield. Increasing irrigation amount and applying nitrogen at 138 kg/hm2 can significantly enhance spring soybean productivity, improving sustainable agricultural development and profitability in the region.